Polymeric monomer, solid electrolyte, preparation method of solid electrolyte, lithium ion battery and electric equipment
By using polymeric monomers containing sulfonate structures in lithium-ion batteries, the problems of unstable battery interface and thermal runaway are solved, and higher thermal safety and rate performance are achieved.
Patent Information
- Application Number
- CN202411752798.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing solid electrolyte materials have problems such as unstable interface contact, local cracks and thermal runaway in lithium-ion batteries, resulting in poor thermal safety of the battery.
A solid electrolyte with high ionic conductivity is prepared by mixing it with an electrolyte solution and an initiator. The polymerized monomer is preferentially reduced and decomposed during the battery charge and discharge cycle to form a stable SEI film, improving interface stability and thermal safety performance.
By introducing sulfonate groups, the quality of the SEI interface mask is significantly improved, the thermal safety performance and rate performance of the battery are improved, and the side reactions and safety risks of the battery are reduced.
Smart Images

Figure CN119569620A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a polymer monomer, a solid electrolyte and a preparation method thereof, a lithium-ion battery and an electrical device. Background Art
[0002] Thermal runaway of lithium batteries is the main cause of lithium battery explosion accidents. Thermal runaway of a single battery can easily lead to a domino effect, eventually causing fires or even explosions in electric vehicles and energy storage power stations. Therefore, prevention and control of thermal runaway of lithium batteries is the key to ensuring the safe use of batteries.
[0003] Existing electrolyte materials cannot meet the high thermal safety requirements of lithium-ion batteries, especially solid-state batteries. Among them, the interface contact between the solid electrolyte and the electrode material is unstable. The contact between the solid electrolyte and the electrode changes from liquid-solid contact under the electrolyte system to solid-solid contact. The solid electrolyte material is very prone to local cracks, and the interface with the electrode will deteriorate, destroying the interface structure and affecting the thermal safety stability of the battery. When the interface film decomposes, the electrolyte and the negative electrode active material will react exothermically, and the lithium salt will also react violently with the electrolyte. The heat and gas generated by these reactions will further promote the thermal runaway process of the battery.
[0004] Therefore, in order to meet the requirements of high thermal safety, the structure of solid electrolyte materials needs to be further optimized and improved. Summary of the invention
[0005] The purpose of the present application is to provide a polymer monomer, a solid electrolyte and a preparation method thereof, a lithium ion battery and an electrical device to solve the above-mentioned problems.
[0006] In order to achieve the above objectives, the present application provides a first aspect of a polymerizable monomer, the structural formula of which is:
[0007]
[0008] Wherein, R0 is selected from a saturated alkyl group, an unsaturated alkyl group, an aromatic group or a group containing a non-carbon atom group;
[0009] R1, R2, R3, R4, R5 and R6 are each independently selected from an acrylic group or a hydroxyl group.
[0010] Optionally, the polymerizable monomer satisfies at least one of the following conditions:
[0011] A. The saturated alkyl group includes Wherein, n1 is any positive integer from 1 to 10;
[0012] B. The unsaturated alkyl group includes and / or
[0013] C. The aromatic group includes and / or
[0014] D. The non-carbon atom-containing group is selected from
[0015] Wherein, n2, n3, n4, n5, and n6 are each independently any positive integer from 1 to 10;
[0016] E. The total number of the acrylic acid groups R1-R6 is 4-6.
[0017] The second aspect of the present application provides a method for preparing the polymerizable monomer, comprising:
[0018] 3,3-bis(hydroxymethyl)-1,3-propanediol, acrylic acid and a catalyst are first mixed and reacted to obtain an acrylic polyol ester precursor;
[0019] The acrylic polyol ester precursor and the disulfonic acid compound are mixed for a second time and reacted for a second time to obtain a polymerized monomer.
[0020] Optionally, the method for preparing the polymerizable monomer satisfies at least one of the following conditions:
[0021] A. the molar ratio of the 3,3-bis(hydroxymethyl)-1,3-propanediol to the acrylic acid is 1:2-4;
[0022] B. The mass of the catalyst is 0.2% to 2% of the total mass of the 3,3-bishydroxymethyl-1,3-propanediol and the acrylic acid;
[0023] C. The molar ratio of the acrylic polyol ester precursor to the disulfonic acid compound is 1.8-2.2:1;
[0024] D. The temperature of the first reaction is 50°C-90°C and the time is 2h-12h;
[0025] E. The temperature of the second reaction is 50°C-90°C, and the time is 2h-12h;
[0026] F. the catalyst comprises dibutyl dilaurate;
[0027] G. The disulfonic acid compound includes one or more of 1,3-propanedisulfonic acid, 1,4-butanedisulfonic acid, 1,4-piperazinediethanesulfonic acid, 1,4-piperazinedipropanesulfonic acid, 1,4-benzenedisulfonic acid or 2,6-naphthalenedisulfonic acid.
[0028] The third aspect of the present application provides a solid electrolyte, wherein the raw materials thereof, calculated by weight, include:
[0029] 95-99 parts of electrolyte, 1-5 parts of polymerization monomer, 0.003-0.15 parts of initiator;
[0030] The polymerizable monomer includes the polymerizable monomer or is prepared by the method for preparing the polymerizable monomer;
[0031] The raw materials of the electrolyte include electrolyte lithium salt and organic solvent.
[0032] Optionally, the solid electrolyte satisfies at least one of the following conditions:
[0033] A. The electrolyte lithium salt includes one or more of ethyl methyl carbonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, propane sultone, and vinyl sulfate;
[0034] B. The electrolyte lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium difluorooxalatoborate;
[0035] C. The raw materials of the electrolyte, calculated based on the total mass as 100%, include:
[0036] Electrolyte lithium salt 10%-20%, organic solvent 80%-90%;
[0037] D. the initiator comprises an azo compound;
[0038] E. The viscosity of the solid electrolyte is 2mPas-7mPas.
[0039] The fourth aspect of the present application provides a method for preparing the solid electrolyte, comprising:
[0040] The raw materials of the solid electrolyte are mixed for the third time to prepare a solid electrolyte.
[0041] Optionally, the method for preparing the solid electrolyte satisfies at least one of the following conditions:
[0042] A. the relative humidity of the third mixture is less than or equal to 2%;
[0043] B. The dew point temperature of the third mixture is less than or equal to -40°C.
[0044] A fifth aspect of the present application provides a lithium-ion battery, comprising the solid electrolyte or prepared by the solid electrolyte preparation method.
[0045] A sixth aspect of the present application provides an electrical device comprising the lithium-ion battery.
[0046] Compared with the prior art, the beneficial effects of this application include:
[0047] The polymerized monomer provided in the present application, firstly, contains a sulfonate structure, which has a low reduction potential and can be reduced and decomposed on the electrode surface in priority to other components in the electrolyte at the early stage of the battery charge and discharge cycle, thereby facilitating the formation of the SEI film. This preferential reduction characteristic enables the sulfonate group to play a key role in the formation of the SEI film; secondly, the two sulfonate groups can be converted into an organic solid electrolyte even with a small amount of polymerized monomer added, and the polymerized monomer is efficiently cross-linked into a three-dimensional network, so that the electrolyte viscosity is low, which can reduce the interfacial wetting problem caused by the increase in viscosity, improve the effective interfacial contact of the electrolyte material with the electrode, and improve The interface stability of the solid-state battery can be improved, thereby improving the thermal safety performance of the battery; then, the introduction of sulfonate groups can significantly improve the quality of the SEI interface film. The sulfonate groups can undergo electrochemical reactions with the active substances on the electrode surface (mainly the negative electrode active substances) to generate stable compounds. The generated compounds can firmly adhere to the electrode surface to form a dense and stable SEI interface film. In the early stage of heat accumulation, the degree of decomposition of the SEI interface film and the heat released can be suppressed. This SEI film can effectively prevent further corrosion of the electrode by solvent molecules and electrolyte salts, and can also reduce the side reactions between the electrode and the electrolyte, thereby improving the safety performance of the battery.
[0048] The method for preparing the polymerizable monomer provided in the present application is simple to operate.
[0049] The solid electrolyte provided in the present application has ion transport performance with high ion conductivity.
[0050] The method for preparing the solid electrolyte provided in the present application is simple to operate.
[0051] The lithium-ion battery and electrical equipment provided in the present application exhibit good rate performance in high-rate charge and discharge, and their electrochemical properties are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0053] Figure 1 This is the infrared spectrum test chart of the polymerized monomer prepared in Example 1;
[0054] Figure 2 This is a comparison chart of the rate performance test of the solid-state batteries prepared in Example 1 and Comparative Example 1;
[0055] Figure 3This is a comparison chart of the hot box test of the solid-state batteries prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0056] As used herein:
[0057] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0058] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0059] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0060] In these examples, parts and percentages are by mass unless otherwise indicated.
[0061] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0062] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0063] In a first aspect, the present application provides a polymerizable monomer, the structural formula of which is:
[0064]
[0065] It should be noted that the SEI film induced by sulfonate compounds is not only stable, thin and dense, but also more beneficial to the electrochemical properties of the battery, such as the high-rate performance.
[0066] It should also be noted that the sulfonate group can react electrochemically with the active substances on the electrode surface (mainly the negative electrode active substances) to form a stable solid electrolyte interface film (SEI film). This is a complex and important process. The sulfonate group improves the quality of the interface film. The introduction of sulfonate groups can significantly improve the quality of the SEI interface film. This group can react electrochemically with the active substances on the electrode surface to generate stable compounds. The generated compounds can firmly adhere to the electrode surface to form a dense and stable SEI interface film. Once the SEI film is stably formed, it can effectively prevent side reactions in the battery and protect the electrode material from being destroyed. It can inhibit the degree of decomposition of the SEI interface film and the heat released in the early stage of heat accumulation. This SEI film can effectively prevent the solvent molecules and electrolyte salts from further corroding the electrode, and can also reduce the side reactions between the electrode and the electrolyte, thereby improving the safety performance of the battery.
[0067] Among them, R0 is selected from saturated alkyl, unsaturated alkyl, aromatic or non-carbon atom-containing groups; these groups can become ideal connecting groups, and they have certain chemical stability, and can stably connect them together without deteriorating the chemical properties of the terminal groups. At the same time, a variety of organic compounds can be formed through different structural connection methods, making the structure and properties of the monomers rich and diverse, making the monomer structure diversifiable, and further enriching the chemical properties of the molecules.
[0068] It should be noted that R0 connects the bulky terminal groups at both ends. The connecting group R0 gives the polymerized monomer a strong preparability and can be synthesized by a variety of methods. The connecting group R0 has a strong chemical bond energy, which effectively connects the bulky terminal groups at both ends and improves the strength and elasticity of the polymer gel. In addition, the introduction of the R0 chemical bond mainly enhances the overall stability of the monomer and polymer structure. Compared with systems connected only by physical effects (such as van der Waals forces, hydrogen bonds, etc.) or other methods, the R0 chemical bond usually has a higher bond energy and chemical bond strength, so the material monomer and polymer structure are more difficult to be destroyed.
[0069] In some embodiments, R0 is selected from saturated alkyl and unsaturated alkyl.
[0070] R1, R2, R3, R4, R5, and R6 are independently selected from acrylic acid or hydroxyl groups, and the bulky end groups R1-R6 on both sides are connected to the main structure through the R0 chemical bond, which can form a more compact and stable structure, reducing the influence of external factors (such as high temperature, external mechanical shock, etc.) on the structure. The bulky end groups connected by the R0 chemical bond have a relatively symmetrical structure and can improve the thermal stability of the material chemical structure. These bulky end groups can absorb and disperse heat when heated, thereby slowing down the thermal decomposition and degradation process of the material. Moreover, the presence of bulky end groups can also reduce the deformation and flow of the material at high temperatures and improve its thermal stability. This is of great significance to the application of organic solid electrolytes in batteries to improve the heat resistance and safety of batteries.
[0071] When R1, R2, R3, R4, R5, and R6 are acrylic groups, they become functional groups of the polymer monomers. If they are hydroxyl groups, they are unreacted groups, the original hydroxyl groups, and cannot provide functionality.
[0072] It should be noted that the acrylic acid group is the functional group of the polymerized monomer provided in this application. Functionality refers to the number of functional groups in a monomer molecule that can participate in the reaction, which is directly related to the reactivity of the reactants and the structural characteristics of the products. Functionality determines the number of active points of the monomer molecule in the reaction, thereby affecting the reaction rate and reaction path; generally speaking, the higher the functionality, the more active points of the monomer molecule in the reaction, the faster the reaction rate, and the greater the probability of the monomer molecule participating in the polymerization reaction and chain growth. Highly functional monomers are more likely to form a highly cross-linked polymer network structure, and each functionality is a reaction site. The dense reaction sites give the monomer a higher reactivity, and polymerization reactions can occur at lower content and concentration to form a polymer network, which makes the proportion of polymerized monomers in solid electrolytes can be compressed to an extremely low level.
[0073] It should also be noted that the acrylic acid group undergoes addition polymerization during the heating process, that is, during the in-situ curing process, it will cross-link with each other to form a polymer gel, which plays a role in the skeleton support of the solid electrolyte and effectively absorbs lithium salts and solvents.
[0074] In some embodiments, the polymerizable monomer satisfies at least one of the following conditions:
[0075] A. The saturated alkyl group includes Wherein, n1 is any positive integer from 1 to 10;
[0076] Optionally, n1 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or any positive integer between 1 and 10;
[0077] B. The unsaturated alkyl group includes and / or
[0078] C. The aromatic group includes and / or
[0079] D. The non-carbon atom-containing group is selected from
[0080] Wherein, n2, n3, n4, n5, and n6 are each independently any positive integer from 1 to 10;
[0081] Optionally, n2, n3, n4, n5, and n6 can each independently be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or any positive integer between 1 and 10;
[0082] E. The total number of the acrylic acid groups R1-R6 is 4-6.
[0083] Optionally, the total number of acrylic acid groups in R1, R2, R3, R4, R5, and R6 may be 4, 5, 6, or any positive integer between 4 and 6;
[0084] It can be understood that the total number of acrylic acid groups in R1, R2, R3, R4, R5, and R6 is 4-6;
[0085] It should be noted that when the number of acrylic acid groups in R1-R6 is higher, the functionality is higher, and polymerization reaction can occur at a lower content and concentration to form a polymer network.
[0086] The second aspect of the present application provides a method for preparing the polymerizable monomer, comprising:
[0087] 3,3-bis(hydroxymethyl)-1,3-propanediol, acrylic acid and a catalyst are first mixed and reacted to obtain an acrylic polyol ester precursor;
[0088] The acrylic polyol ester precursor and the disulfonic acid compound are mixed for a second time and reacted for a second time to obtain a polymerized monomer.
[0089] In some embodiments, the method for preparing the polymerizable monomer satisfies at least one of the following conditions:
[0090] A. the molar ratio of the 3,3-bishydroxymethyl-1,3-propanediol to the acrylic acid is 1:2-4;
[0091] Optionally, the molar ratio of 3,3-bishydroxymethyl-1,3-propanediol to acrylic acid may be 1:2, 1:3, 1:4 or any value between 1:2 and 4;
[0092] B. The mass of the catalyst is 0.2% to 2% of the total mass of the 3,3-bishydroxymethyl-1,3-propanediol and the acrylic acid;
[0093] Optionally, the mass of the catalyst may be 0.2%, 0.5%, 1%, 1.5%, 2% or any value between 0.2% and 2% of the total mass of 3,3-bishydroxymethyl-1,3-propanediol and acrylic acid;
[0094] C. The molar ratio of the acrylic polyol ester precursor to the disulfonic acid compound is 1.8-2.2:1;
[0095] Optionally, the molar ratio of the acrylic polyol ester precursor to the disulfonic acid compound may be 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1 or any value between 1.8 and 2.2:1;
[0096] D. The temperature of the first reaction is 50°C-90°C and the time is 2h-12h;
[0097] Optionally, the temperature of the first reaction can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value between 50°C and 90°C, and the time can be 2h, 4h, 6h, 8h, 10h, 12h or any value between 2h and 12h;
[0098] E. The temperature of the second reaction is 50°C-90°C, and the time is 2h-12h;
[0099] Optionally, the temperature of the second reaction can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value between 50°C and 90°C, and the time can be 2h, 4h, 6h, 8h, 10h, 12h or any value between 2h and 12h;
[0100] F. the catalyst comprises dibutyl dilaurate;
[0101] G. The disulfonic acid compound includes one or more of 1,3-propanedisulfonic acid, 1,4-butanedisulfonic acid, 1,4-piperazinediethanesulfonic acid, 1,4-piperazinedipropanesulfonic acid, 1,4-benzenedisulfonic acid or 2,6-naphthalenedisulfonic acid.
[0102] The third aspect of the present application provides a solid electrolyte, wherein the raw materials thereof, calculated by weight, include:
[0103] 95-99 parts of electrolyte, 1-5 parts of polymerization monomer, 0.003-0.15 parts of initiator;
[0104] Optionally, the raw materials of the solid electrolyte are measured by weight, the electrolyte can be 95 parts, 96 parts, 97 parts, 98 parts, 99 parts or any value between 95 parts and 99 parts, the polymerizable monomer can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts or any value between 1 part and 5 parts, and the initiator can be 0.003 parts, 0.005 parts, 0.01 parts, 0.1 parts, 0.15 parts or any value between 0.003 parts and 0.15 parts;
[0105] It should be noted that, since the polymerized monomers form bulk molecules after polymerization, the movement of bulk molecules is more difficult than that of small molecules in the electrolyte solvent and lithium salt anions and cations, and lithium-ion batteries are inevitably limited under this condition. However, the amount of polymerized monomer added in this application is relatively low, which can reduce its hindrance to the high-speed conduction of lithium ions and can maintain the comprehensive ionic conductivity of the electrolyte at a high level.
[0106] The polymerizable monomer includes the polymerizable monomer or is prepared by the method for preparing the polymerizable monomer;
[0107] It should be noted that the solid electrolyte formed by the introduction of polymerized monomers into the solid electrolyte should essentially be an organic solid electrolyte prepolymer. After the prepolymer is heated and cured, it forms an organic solid electrolyte in a gel state. Before heating and curing, the low viscosity of the prepolymer is beneficial to its wetting of the internal pole piece of the battery and the interfacial electrochemical reaction of the active particles in the pole piece, which is crucial to improving the interfacial stability of the solid-state battery and the thermal safety performance of the battery.
[0108] The raw materials of the electrolyte include electrolyte lithium salt and organic solvent.
[0109] In some embodiments, the solid electrolyte satisfies at least one of the following conditions:
[0110] A. The electrolyte lithium salt includes one or more of ethyl methyl carbonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, propane sultone, and vinyl sulfate;
[0111] B. The electrolyte lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium difluorooxalatoborate;
[0112] C. The raw materials of the electrolyte, calculated based on the total mass as 100%, include:
[0113] Electrolyte lithium salt 10%-20%, organic solvent 80%-90%;
[0114] Optionally, the raw materials of the electrolyte are calculated based on the total mass of 100%, the electrolyte lithium salt can be 10%, 15%, 20% or any value between 10% and 20%, and the organic solvent can be 80%, 85%, 90% or any value between 80% and 90%;
[0115] D. the initiator comprises an azo compound;
[0116] In some embodiments, the azo compound includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate;
[0117] E. The viscosity of the solid electrolyte is 2mPas-7mPas.
[0118] Optionally, the viscosity of the solid electrolyte before heating and curing may be 2 mPas, 3 mPas, 4 mPas, 5 mPas, 6 mPas, 7 mPas or any value between 2 mPas and 7 mPas.
[0119] The fourth aspect of the present application provides a method for preparing the solid electrolyte, comprising:
[0120] The raw materials of the solid electrolyte are mixed for the third time to prepare a solid electrolyte.
[0121] In some embodiments, the electrolyte prepolymer is mixed and injected into the battery system of the positive electrode, separator and negative electrode, pre-sealed and left to stand at room temperature, soaked for 24h-72h, and then heated and cured at 40℃-80℃ for 12h-72h. During the heating, the prepolymer reacts inside the dry battery cell to obtain an organic solid electrolyte by in-situ thermal curing.
[0122] In some embodiments, the method for preparing the solid electrolyte satisfies at least one of the following conditions:
[0123] A. the relative humidity of the third mixture is less than or equal to 2%;
[0124] Optionally, the relative humidity of the third mixture may be 0.01%, 0.1%, 1%, 2%, or any value less than or equal to 2%;
[0125] B. The dew point temperature of the third mixture is less than or equal to -40°C.
[0126] Optionally, the dew point temperature of the third mixture may be -100°C, -80°C, -60°C, -40°C, or any value less than or equal to -40°C.
[0127] It should be noted that the dew point temperature refers to the temperature at which the air is cooled to saturation under the condition that the water vapor content in the air remains unchanged and the air pressure is kept constant. It is called the dew point temperature, or dew point for short, and is expressed in ℃ or ℉. In fact, it is the temperature at which water vapor and water reach equilibrium.
[0128] A fifth aspect of the present application provides a lithium-ion battery, comprising the solid electrolyte or prepared by the solid electrolyte preparation method.
[0129] In some embodiments, the lithium-ion battery further comprises a positive electrode sheet and a negative electrode sheet;
[0130] The raw materials of the positive electrode sheet are calculated based on 100% of the total mass, including:
[0131] The positive electrode active material is 80%-95%, the conductive agent is 1%-10%, the binder is 1%-10%, and the balance is an organic solvent.
[0132] The positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide and nickel-cobalt-manganese ternary positive electrode, preferably high-nickel ternary positive electrode NCM811;
[0133] Conductive agents include acetylene black;
[0134] The binder includes polyvinylidene fluoride (PVDF);
[0135] The organic solvent includes 1-methyl-2-pyrrolidone (NMP).
[0136] The raw materials of the negative electrode sheet are calculated based on 100% of the total mass, including:
[0137] The negative electrode active material is 80%-95%, the conductive agent is 1%-10%, the binder is 1%-5%, the additive is 1%-5%, and the balance is the solvent.
[0138] The negative electrode active material includes a silicon-carbon composite material;
[0139] Conductive agents include carbon black (SP);
[0140] The binder includes sodium carboxymethyl cellulose (CMC);
[0141] Additives include polystyrene butadiene copolymer (SBR);
[0142] The solvent includes water.
[0143] A sixth aspect of the present application provides an electrical device comprising the lithium-ion battery.
[0144] In some embodiments, the electrical equipment includes, but is not limited to, one or more of electric vehicles, electric bicycles, smart home devices, robots, heavy trucks, ships, and energy storage systems.
[0145] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0146] Example 1
[0147] In a first aspect, the present embodiment provides a polymerizable monomer, whose structural formula is:
[0148]
[0149] This is equivalent to the general structural formula in which n1 is 3 and R1-R6 are all acrylic acid groups.
[0150] A second aspect of this embodiment provides a method for preparing the above-mentioned polymerizable monomer, comprising:
[0151] 2 mol of 2,2-bishydroxymethyl-1,3-propanediol and 6 mol of acrylic acid were uniformly stirred, and 0.5 wt% of dibutyltin dilaurate in the total weight of the 2,2-bishydroxymethyl-1,3-propanediol and acrylic acid was added as a catalyst, and stirred at 60° C. for 6 h to obtain a precursor;
[0152] The above precursor was then evenly stirred with 1 mol of 1,3-propanedisulfonic acid, reacted at 60° C. for 4 h, and finally cooled to room temperature, filtered through an alumina column, washed with deionized water for 3 times, and distilled under reduced pressure to obtain the target product, a polymerization monomer.
[0153] The infrared spectrum test of the polymerized monomer is as follows Figure 1 As shown, at 1346cm -1 There is an absorption peak, which is the stretching vibration peak of the sulfonate group, at 1721cm -1 An absorption peak appears, which is the stretching vibration peak of the carbonyl group, which is the characteristic peak of the carbonyl group in acrylate, 1164cm -1 These infrared absorption peaks are the CO stretching vibration peaks in acrylate. These infrared absorption peaks all prove the chemical structure of the polymerized monomer.
[0154] A third aspect of this embodiment provides a solid electrolyte, wherein the raw materials thereof, calculated by weight, include:
[0155] 97g electrolyte, 3g polymerization monomer 1, 0.03g initiator azobisisobutyronitrile;
[0156] Among them, the electrolyte includes 35g ethyl methyl carbonate, 19g ethylene carbonate, 15g propylene carbonate, 10g fluoroethylene carbonate, 1g propane sultone, 2g vinyl sulfate, 10g lithium hexafluorophosphate, 4g lithium bis(fluorosulfonyl)imide, 0.5g lithium difluorophosphate, and 0.5g lithium difluorooxalatoborate.
[0157] A fourth aspect of this embodiment provides a method for preparing a solid electrolyte, comprising:
[0158] The above raw materials are mixed uniformly at room temperature, relative humidity below 2%, and dew point below -40°C.
[0159] A fifth aspect of the present embodiment provides a sodium ion battery and a method for preparing the same, including:
[0160] Positive electrode preparation method: grind and mix 95% by mass of positive electrode active material high nickel ternary positive electrode NCM811 and 2% by mass of conductive agent acetylene black, add 3% by mass of polyvinylidene fluoride PVDF dispersed in solvent 1-methyl-2-pyrrolidone NMP, grind and mix to obtain positive electrode material, wherein NMP is used for mixing, dispersing and adjusting the viscosity of the slurry, and volatilizes during drying, so it is not included in the mass percentage of the positive electrode material; the positive electrode material is coated on the surface of aluminum foil, and dried to obtain the positive electrode.
[0161] Preparation method of negative electrode sheet: 95% silicon-carbon composite negative electrode material is added to 1.5% conductive carbon black SP by mass, and ground and mixed, 1.5% sodium carboxymethyl cellulose CMC by mass and 2% polystyrene butadiene copolymer SBR by mass are added and dispersed in solvent water, ground and dispersed, and coated on the surface of copper foil, and dried to obtain negative electrode sheet. The diaphragm is a porous support material that isolates the positive and negative electrodes, and can be polyethylene diaphragm, polypropylene diaphragm, polytetrafluoroethylene non-woven fabric, etc.
[0162] The solid electrolyte was injected into the dry battery cell assembled with positive and negative electrode sheets and diaphragms, pre-sealed with a heat plastic sealing machine, left to stand at room temperature for 24 hours, then placed in a hot oven, slowly heated to 50°C, and reacted for 12 hours. During the heating, the solid electrolyte reacted inside the dry battery cell, and an organic solid electrolyte was obtained by in-situ thermal curing to prepare a solid-state battery. The solid-state battery was charged and discharged, and the battery performance was tested.
[0163] Example 2
[0164] The difference from Example 1 is that n1 is 7 and the structural formula is:
[0165]
[0166] Example 3
[0167] The difference from Example 1 is that R0 is The structural formula is:
[0168]
[0169] Example 4
[0170] The difference from Example 1 is that R0 is The structural formula is:
[0171]
[0172] Example 5
[0173] The difference from Example 1 is that R0 is an unsaturated alkyl group, and the specific structural formula is:
[0174]
[0175] Example 6
[0176] The difference from Example 1 is that R0 is a non-carbon atom-containing group, and the structural formula is:
[0177]
[0178] Example 7
[0179] The difference from Example 6 is that n2 is 1 and the structural formula is:
[0180]
[0181] Example 8
[0182] The difference from Example 1 is that R0 is a non-carbon atom-containing group, and the structural formula is:
[0183]
[0184] Example 9
[0185] The difference from Example 1 is that R0 is a non-carbon atom-containing group, and the structural formula is:
[0186]
[0187] Example 10
[0188] The difference from Example 1 is that R0 is a non-carbon atom-containing group, and the structural formula is:
[0189]
[0190] Embodiment 11
[0191] The difference from Example 1 is that the number of acrylic acid groups is 4, and the structural formula is:
[0192]
[0193] Example 12
[0194] The difference from Example 1 is that the amount of polymerization monomer used is 5 g.
[0195] Embodiment 13
[0196] The difference from Example 1 is that the specific components of the electrolyte are 32g of dimethyl carbonate, 6g of ethyl methyl carbonate, 20g of ethylene carbonate, 15g of propylene carbonate, 10g of fluoroethylene carbonate, 0.2g of vinylene carbonate, 0.5g of adiponitrile, 12.5g of lithium hexafluorophosphate, and 0.8g of lithium bis(oxalatoborate).
[0197] Embodiment 14
[0198] The difference from Example 1 is that the initiator is dimethyl azobisisobutyrate.
[0199] Embodiment 15
[0200] The difference from Example 1 is that the solid electrolyte is injected into the battery system, pre-sealed and left to stand at room temperature, soaked for 72 hours, and then heated and cured at 65° C. for 24 hours to obtain a solid-state battery.
[0201] Comparative Example 1
[0202] The difference from Example 1 is that the polymerized monomer has no sulfate group, and the structural formula is:
[0203]
[0204] Comparison of the results of the rate performance test (3C / 0.2C discharge capacity retention rate) of the solid-state batteries prepared in Comparative Example 1 and Example 1 Figure 2 As shown, the capacity retention rate of the 3C high-rate discharge of Example 1 is higher, and the solid electrolyte prepared in Example 1 makes the active particle interface stable and dense, and the ion transmission is more efficient, thereby improving the rate performance of the whole battery.
[0205] Comparison of the results of the full battery hot box test of the solid-state batteries prepared in Comparative Example 1 and Example 1 Figure 3 As shown, the battery of Comparative Example 1 experienced thermal runaway in a 150°C hot box and the temperature rose sharply. The solid-state battery corresponding to Example 1 continued to be heated after the hot box temperature reached 150°C, and the temperature remained stable, and no thermal runaway occurred. This shows that Example 1 can maintain normal operation inside the battery when the whole battery is continuously heated in a high-temperature hot box. The solid-state electrolyte of Example 1 can improve the thermal stability of the material, greatly stabilize the electrochemical structure inside the battery, and improve the thermal safety of the battery.
[0206] Comparative Example 2
[0207] The difference from Example 10 is that the polymerized monomer has no sulfate group, and the structural formula is:
[0208]
[0209] Comparative Example 3
[0210] The difference from Example 10 is that the number of sulfate groups is 2, and the structural formula is:
[0211]
[0212] The polymerized monomers, solid electrolytes and solid batteries prepared in the above examples and comparative examples were subjected to performance tests, and the specific test results are shown in Table 1.
[0213] Among them, infrared spectrum test: place the sample to be tested on the crystal surface of the optical platform of the infrared spectrometer ATR (model is20), open the infrared ATR test software, and set the test parameters, the resolution is 4, the number of scans is set to 32, and after starting the test instrument, rotate the knob above the reflector to press the sample to be tested so that it is fully in contact with the emission hole below, and start collecting data. After the test is completed, the infrared spectrum information of the sample can be obtained.
[0214] Viscosity test: Use NDJ-5S digital display rotary viscometer to test the viscosity of organic solid electrolyte prepolymer. Pour the prepolymer into a flat-bottom container with a diameter greater than 60mm. Maintain the prepolymer temperature at 25°C and keep the operating table stable and vibration-free. Screw the instrument protection frame into the lower end of the instrument in reverse direction. Use the L0 rotor to screw into the instrument universal joint counterclockwise. Rotate the lifting knob to slowly immerse the rotor in the prepolymer until the rotor liquid level mark, that is, the groove scale, is in the same plane as the liquid surface. Adjust the instrument level again. Press the rotor selection key, select the speed and press the OK key. The rotor starts to rotate. After the displayed value stabilizes, press the stop key to read the viscosity value.
[0215] Conductivity test: Place the electrode ring that fixes the electrolyte container and the polytetrafluoroethylene single ring that serves as the electrolyte container at the bottom of the battery shell, then drop the prepolymer solution to be tested into the electrolyte container so that the electrolyte completely fills the chamber of the electrolyte container, cover it with a stainless steel electrode plug to form a blocking electrode; finally, cover the upper cover of the battery shell, tighten the butterfly nut, and complete the assembly of the battery. The assembled blocking battery is directly connected to the electrochemical workstation (VMP-3e, Bio-Logic) and placed in a 50°C constant temperature box. The battery is cured at high temperature, and an AC impedance test is performed at a frequency of 1MHz-0.03Hz. The battery is tested by EIS. According to σ=L / (R×S), σ is the ionic conductivity, L is the electrolyte thickness, S is the area of contact between the electrolyte membrane and the electrode, and R is the impedance measured by the impedance meter. The above formula is used to calculate the ionic conductivity (σ, mS / cm) of the solid electrolyte.
[0216] Rate performance test: After standing for 10 minutes, the battery was charged to 4.2V at a constant current of 0.2C, and the charge was stopped at a constant voltage of 4.2V until the current dropped to 0.05C; after standing for 10 minutes, the battery was discharged at a discharge rate of 0.2C until the battery voltage reached the set termination voltage of 2.75V, and the discharge capacity was recorded. The above steps were repeated 5 times to obtain the average value C1 of the 0.2C discharge capacity; the above steps were repeated again, except that the discharge rate was 3C, and the charge and discharge steps were repeated 5 times to obtain the average value C2 of the 3C rate discharge capacity, and the ratio of C2 / C1 was calculated to evaluate the rate performance.
[0217] Safety test: In the hot box test, the lithium battery is fully charged and placed in the test box. The heating temperature rate is set to 5℃ / min. The battery is heated from room temperature to a high temperature of 150℃ and is heated constantly at 150℃ for 30 minutes. The hot box safety performance is evaluated by observing the performance of the battery during the experiment, such as whether it catches fire, explodes, leaks, etc. If the battery catches fire, explodes, leaks, etc. during the heating process, it is considered to have failed. Otherwise, it is considered to have passed the hot box test. The hot box safety performance of 10 full batteries in each batch is tested, and the hot box safety test pass rate is calculated.
[0218] Table 1 Performance test
[0219]
[0220]
[0221] As can be seen from Table 1, the viscosity in the embodiment is relatively low. The low viscosity of the prepolymer solution is beneficial to its wetting in the internal pole piece of the battery and the interfacial electrochemical reaction of the active particles in the pole piece, which is crucial to improving the interfacial stability of the solid-state battery and the thermal safety performance of the battery. Furthermore, the conductivity in the embodiment is significantly higher than that in the comparative example, and the ion transport performance with high ionic conductivity can enable the full battery to exhibit good rate performance in high-rate charge and discharge, thereby improving the electrochemical performance of the full battery.
[0222] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0223] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A polymerizable monomer, characterized in that: Its general structural formula is: Wherein, R0 is selected from one of the following groups: a saturated alkyl group, an unsaturated alkyl group, an aromatic group or a group containing a non-carbon atom group; R1, R2, R3, R4, R5 and R6 are each independently selected from an acrylic group or a hydroxyl group.
2. The polymerizable monomer according to claim 1, characterized in that At least one of the following conditions is met: A. The saturated alkyl group includes Wherein, n1 is any positive integer from 1 to 10; B. The unsaturated alkyl group includes and / or C. The aromatic group includes and / or D. The non-carbon atom-containing group is selected from One of the following; Wherein, n2, n3, n4, n5, and n6 are each independently any positive integer from 1 to 10; E. The total number of the acrylic acid groups R1-R6 is 4-6.
3. A method for preparing a polymerizable monomer according to claim 1 or 2, characterized in that: include: 3,3-bis(hydroxymethyl)-1,3-propanediol, acrylic acid and a catalyst are first mixed and reacted to obtain an acrylic polyol ester precursor; The acrylic polyol ester precursor and the disulfonic acid compound are mixed for a second time and reacted for a second time to obtain a polymerized monomer.
4. The method for preparing a polymerizable monomer according to claim 3, characterized in that: At least one of the following conditions is met: A. the molar ratio of the 3,3-bis(hydroxymethyl)-1,3-propanediol to the acrylic acid is 1:2-4; B. The mass of the catalyst is 0.2% to 2% of the total mass of the 3,3-bishydroxymethyl-1,3-propanediol and the acrylic acid; C. The molar ratio of the acrylic polyol ester precursor to the disulfonic acid compound is 1.8-2.2:1; D. The temperature of the first reaction is 50°C-90°C and the time is 2h-12h; E. The temperature of the second reaction is 50°C-90°C, and the time is 2h-12h; F. the catalyst comprises dibutyl dilaurate; G. The disulfonic acid compound includes one or more of 1,3-propanedisulfonic acid, 1,4-butanedisulfonic acid, 1,4-piperazinediethanesulfonic acid, 1,4-piperazinedipropanesulfonic acid, 1,4-benzenedisulfonic acid or 2,6-naphthalenedisulfonic acid.
5. A solid electrolyte, characterized in that: The raw materials, calculated by mass, include: 95-99 parts of electrolyte, 1-5 parts of polymerization monomer, 0.003-0.15 parts of initiator; The polymerizable monomer includes the polymerizable monomer described in claim 1 or 2 or is prepared by the method for preparing the polymerizable monomer described in claim 3 or 4; The raw materials of the electrolyte include electrolyte lithium salt and organic solvent.
6. The solid electrolyte according to claim 5, characterized in that At least one of the following conditions is met: A. The electrolyte lithium salt includes one or more of ethyl methyl carbonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, propane sultone, and vinyl sulfate; B. The electrolyte lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium difluorooxalatoborate; C. The raw materials of the electrolyte, calculated based on the total mass as 100%, include: Electrolyte lithium salt 10%-20%, organic solvent 80%-90%; D. the initiator comprises an azo compound; E. The viscosity of the solid electrolyte is 2mPas-7mPas.
7. A method for preparing a solid electrolyte according to claim 5 or 6, characterized in that: include: The raw materials of the solid electrolyte are mixed for the third time to prepare a solid electrolyte.
8. The method for preparing a solid electrolyte according to claim 7, characterized in that: At least one of the following conditions is met: A. the relative humidity of the third mixture is less than or equal to 2%; B. The dew point temperature of the third mixture is less than or equal to -40°C.
9. A lithium ion battery, characterized in that: The solid electrolyte comprises the solid electrolyte described in claim 5 or 6 or is prepared by the preparation method of the solid electrolyte described in claim 7 or 8.
10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.
Citation Information
Patent Citations
Additive for nonaqueous electrolyte, nonaqueous electrolyte, and electricity storage device
CN103004006A
High-safety solid-state electrolyte, preparation method and application thereof
CN111969245A
Organic solid electrolyte material, silicon-based solid-state battery and preparation method and application of silicon-based solid-state battery
CN118791655A
Photosensitive resin composition
JP1987052547A
Non-aqueous electrolyte and secondary battery using the same
KR1020090040214A